An alternative test of the trade-off theory of capital structure - Giorgio Canarella; Mahmoud Nourayi; Michael J. Sullivan (Contemporary Economics, 2014)
The purpose of this paper is to investigate the stochastic behavior of corporate debt ratios utilizing a balanced panel of 2,556 publicly traded US firms during the period 1997 - 2010. We partition the panel into ten economic sectors and perform panel unit root tests on each sector employing book value and market value measures of debt ratio. First-generation panel unit root tests provide consistent evidence that debt ratios are mean reverting, which supports the trade-off theory. However, these tests rely on the assumption that the debt ratios are cross-sectionally independent, but tests of cross-sectional independence fail to uphold this assumption. Thus, utilizing a second-generation panel unit root test that controls for cross-sectional dependence, we uncover evidence showing that debt ratios are not mean reverting, which contradicts the trade-off hypothesis. We find that the recent macroeconomic developments triggered by the financial crisis and the Great Recession have considerable explanatory power over the dynamics of the debt ratios. In fact, when we exclude the years of the recent global financial crisis, the unit root hypothesis is rejected in one half of the sectors. We interpret these results as indicative that the recent global events may have produced in these sectors a structural change in the underlying data generation process (DGP). Overall, then, we find mixed evidence on the stationarity of debt ratios.
Keywords: G30; G32; 330; panel unit root tests; capital structure theories; cross-sectional dependence; debt ratio